Analysis of the ecosystem services of mangrove to aquaculture and fisheries in Vietnam - Mangrove and Fishery in the Mekong River Delta, Vietnam - Truong, Dang Thuy (University of Gothenburg, 2021)
In this study, which will cover six provinces in south Vietnam, we expect to find out the optimal level of mangrove coverage for shrimp farming systems, considering the benefits of mangrove on fishery. Besides, investigation of the determinants of the behavior of converting mangrove to other uses will provide useful information for policy makers towards a better management and conservation of mangrove forests. The project has the following research objectives: (1) Examine the impacts of mangrove on shrimp farming, specifically the impacts of mangrove coverage on shrimp farming productivity and profitability; (2) Examine the impacts of mangrove on the risk of shrimp farming; (3) Estimate the mangrove-fishery linkage; (4) Investigate the determinants of mangrove conversion.

We collected data in field trips to villages across the southern coast of Vietnam. The first wave of data was collected from August 2014 to April 2015. The second wave was conducted in 2017, from September to December. Our final sample includes 950 observations from 431 households living and fishing across 11 communes from six provinces including Bac Lieu, Ben Tre, Ca Mau, Kien Giang, Soc Trang and Tra Vinh. Two sources of mangrove forest areas of communes are used. One is reported by the Forestry Management, and the other is calculated using satellite images.

In this study, which will cover six provinces in south Vietnam, we expect to find out the optimal level of mangrove coverage for shrimp farming systems, considering the benefits of mangrove on fishery. Besides, investigation of the determinants of the behavior of converting mangrove to other uses will provide useful information for policy makers towards a better management and conservation of mangrove forests. The project has the following research objectives: (1) Examine the impacts of mangrove on shrimp farming, specifically the impacts of mangrove coverage on shrimp farming productivity and profitability; (2) Examine the impacts of mangrove on the risk of shrimp farming; (3) Estimate the mangrove-fishery linkage; (4) Investigate the determinants of mangrove conversion.

We collected data in field trips to villages across the southern coast of Vietnam. The first wave of data was collected from August 2014 to April 2015. The second wave was conducted in 2017, from September to December. Our final sample includes 950 observations from 431 households living and fishing across 11 communes from six provinces including Bac Lieu, Ben Tre, Ca Mau, Kien Giang, Soc Trang and Tra Vinh. Two sources of mangrove forest areas of communes are used. One is reported by the Forestry Management, and the other is calculated using satellite images.
Analysis of the ecosystem services of mangrove to aquaculture and fisheries in Vietnam - Mangrove and Fishery in the Mekong River Delta, Vietnam
Keywords: fishery; fiskeri; mangrove forest; profitability; lönsamhet; Environmental Sciences; Miljövetenskap; Economics and Business; Ekonomi och näringsliv; Farming; Areella näringar; Economy; Ekonomi; Environment; Miljö